ACCERBATIN, a small molecule at the intersection of auxin and reactive oxygen species homeostasis with herbicidal properties - Hu, Yuming; Depaepe, Thomas; Smet, Dajo; Hoyerova, Klara; Klíma, Petr; Cuypers, Ann; Cutler, Sean; Buyst, Dieter; Morreel, Kris; Boerjan, Wout; Martins, José; Petrášek, Jan; et al. (Journal of Experimental Botany, 2017)
The volatile two-carbon hormone ethylene acts in concert with an array of signals to affect etiolated seedling development. From a chemical screen, we isolated a quinoline carboxamide designated ACCERBATIN (AEX) that exacerbates the 1-aminocyclopropane-1-carboxylic acid-induced triple response, typical for ethylene-treated seedlings in darkness. Phenotypic analyses revealed distinct AEX effects including inhibition of root hair development and shortening of the root meristem. Mutant analysis and reporter studies further suggested that AEX most probably acts in parallel to ethylene signaling. We demonstrated that AEX functions at the intersection of auxin metabolism and reactive oxygen species (ROS) homeostasis. AEX inhibited auxin efflux in BY-2 cells and promoted indole-3-acetic acid (IAA) oxidation in the shoot apical meristem and cotyledons of etiolated seedlings. Gene expression studies and superoxide/hydrogen peroxide staining further revealed that the disrupted auxin homeostasis was accompanied by oxidative stress. Interestingly, in light conditions, AEX exhibited properties reminiscent of the quinoline carboxylate-type auxin-like herbicides. We propose that AEX interferes with auxin transport from its major biosynthesis sites, either as a direct consequence of poor basipetal transport from the shoot meristematic region, or indirectly, through excessive IAA oxidation and ROS accumulation. Further investigation of AEX can provide new insights into the mechanisms connecting auxin and ROS homeostasis in plant development and provide useful tools to study auxin-type herbicides.
Keywords: homeostáza; chinolony; herbicidy; Quinolones; Arabidopsis Proteins; Amino Acids, Cyclic; Indoleacetic Acids; aminokyseliny cyklické; Homeostasis; Reactive Oxygen Species; proteiny huseníčku; Ethylenes; kyseliny indoloctové; reaktivní formy kyslíku; ethyleny; exprese genu; Arabidopsis; semenáček; Seedlings; Herbicides; Gene Expression